Selective expression and significance of ACKR2 in lung aerocytes - Alberto Mantovani; Gianluigi Condorelli; Raffaella Bonecchi; Massimo Locati; Marina Sironi; Roberta Carriero; Francesca Albano; Valeria Mollica Poeta; Lucia Zotti; Alessandra Castagna; Arianna Felicetta; Alessandro Mesaglio; et al. (Journal for ImmunoTherapy of Cancer)
Background ACKR2 is an atypical chemokine receptor that plays a significant role in regulating inflammation by binding to inflammatory CC chemokines and facilitating their degradation. Previous findings suggest that the genetic absence of ACKR2 leads to heightened tumor growth in inflammation-driven models. Conversely, mice lacking ACKR2 exhibit protection against lung metastasis in melanoma and breast cancer models. This study aims to explore the specific cell types expressing ACKR2 and their relative contributions to the protection against lung metastasis.Methods ACKR2 expression was studied by the generation of an inducible and conditional knockout (KO) mouse expressing two reporter genes, luciferase and TdTomato visible by In Vivo Imaging System, flow cytometry and immunofluorescence. Gene expression in lung endothelial cells (ECs) was investigated by RNA sequencing analysis. In vivo models of lung metastasis and inflammation were performed in wild-type (WT) and conditional KO mice by intravenous injection of melanoma and colon cancer cell lines; the induction of acute lung injury model was done by intranasal injection of lipopolysaccharide (LPS). Leukocytes infiltrating lung metastasis were studied by fluorescence-activated cell sorting (FACS) analysis. The serum chemokine levels were studied with a multiplex ELISA.Results The analysis of the reporter mouse revealed that ACKR2 is expressed by lymphatic endothelial cells (LECs) in most murine organs. However, uniquely in the lungs, ACKR2 expression is observed in blood endothelial cells (BECs), specifically in capillaries known as aerocytes specialized for regulating leukocyte trafficking. Selective deletion of Ackr2 from ECs (ACKR2ΔCdh5 mice) but not from LECs (ACKR2ΔProx1 mice) resulted in protection in models of melanoma and colorectal cancer lung metastasis. This protection was associated with an increased presence of activated T lymphocytes infiltrating the lungs compared with WT mice. Additionally, in a model of acute lung injury, mice with selective deletion from the endothelial compartment exhibited heightened extravasation of T lymphocytes compared with both ACKR2 KO and WT mice.Conclusions These results indicate that ACKR2 is selectively expressed by lung vascular capillaries (aerocytes) that are devoted to the regulation of leukocyte extravasation. Selective ACKR2 targeting in this compartment, by modulating chemokine availability, promotes T lymphocyte extravasation resulting in reduced lung metastases.